High performance companies : successful strategies from the world's top achievers - Pangarkar, Nitin (John Wiley & Sons, 2012)
Presents the easy-to-adopt strategies that make companies from Coca-Cola to Starbucks perennial over performers, proposing a number of rules of thumb (or principles) that companies can consider when making their day-to-day decisions which, in turn, can